2007
DOI: 10.1093/glycob/cwm064
|View full text |Cite
|
Sign up to set email alerts
|

The rainbow trout CMP-sialic acid synthetase utilises a nuclear localization signal different from that identified in the mouse enzyme

Abstract: The terminal sugar sialic acid (Sia) plays a pivotal role in cell-cell interaction and recognition. A prerequisite for the biosynthesis of sialoglycoconjugates is the activation of Sia to cytidine monophosphate-Sia (CMP-Sia), by CMP-Sia synthetases (CMP-Sia-syn). CMP-Sia-syn are conserved from bacteria to man, and have been found to reside in the nucleus of all vertebrate species analysed to date. We previously cloned the CMP-Sia-syn from rainbow trout (rt) and identified three clusters of basic amino acids (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Deletion of the central basic cluster (Figs. 1 and 7) abolished enzymatic activity as reported for mouse (14), rainbow trout (15), and zebrafish CMAS enzymes (this study). X-ray analysis of the enzymatically active domain of murine CMAS confirmed that this amino acid stretch is part of the active site (31).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Deletion of the central basic cluster (Figs. 1 and 7) abolished enzymatic activity as reported for mouse (14), rainbow trout (15), and zebrafish CMAS enzymes (this study). X-ray analysis of the enzymatically active domain of murine CMAS confirmed that this amino acid stretch is part of the active site (31).…”
Section: Discussionsupporting
confidence: 85%
“…So far, vertebrate CMAS enzymes, independent of tissue or species, have been predominantly found in nuclear fractions with just minor amounts in other compartments (11,13). Nuclear sequestration has been confirmed with recombinant proteins in different cellular systems (15,41,42). In this study, we identified and characterized the first cytosolic vertebrate CMAS.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The amino acid sequence of this UDP-Gal transporter is similar to that of human UDP-GlcNAc transporter (3); however, it does not transport UDP-GlcNAc (20). CMPNeu5Ac is synthesized in the nucleus in mammalian cells (22)(23)(24), and it is believed that CMP-Neu5Ac is transported through the cytoplasm to the Golgi by a speciˆc transporter. However, since Drosophila CMP-SAS is localized to the Golgi (19), insect cells may not require a speciˆc transporter for CMP-Neu5Ac.…”
Section: C-2 Nucleotide Sugar Transportermentioning
confidence: 99%